The Shc protein Rai enhances T‐cell survival under hypoxia. Issue 11 (15th January 2020) - Criscuoli, Mattia; Ulivieri, Cristina; Filippi, Irene; Monaci, Sara; Guerrini, Giuditta; Crifò, Bianca; De Tommaso, Domiziana; Pelicci, Giuliana; Baldari, Cosima T.; Taylor, Cormac T.; Carraro, Fabio; Naldini, Antonella
Abstract: Hypoxia occurs in physiological and pathological conditions. T cells experience hypoxia in pathological and physiological conditions as well as in lymphoid organs. Indeed, hypoxia‐inducible factor 1α (HIF‐1α) affects T cell survival and functions. Rai, an Shc family protein member, exerts pro‐survival effects in hypoxic neuroblastoma cells. Since Rai is also expressed in T cells, we here investigated its role in hypoxic T cells. In this work, hypoxia differently affected cell survival, proapoptotic, and metabolic programs in T cells, depending upon Rai expression. By using Jurkat cells stably expressing Rai and splenocytes from Rai −/− mice, we demonstrated that Rai promotes T cell survival and affects cell metabolism under hypoxia. Upon exposure to hypoxia, Jurkat T cells expressing Rai show (a) higher HIF‐1α protein levels; (b) a decreased cell death and increased Akt/extracellular‐signal‐regulated kinase phosphorylation; (c) a decreased expression of proapoptotic markers, including caspase activities and poly(ADP‐ribose) polymerase cleavage; (d) an increased glucose and lactate metabolism; (e) an increased activation of nuclear factor‐kB pathway. The opposite effects were observed in hypoxic splenocytes from Rai −/− mice. Thus, Rai plays an important role in hypoxic signaling and may be relevant in the protection of T cells against hypoxia. Abstract : The adapter protein ShcC/Rai protects T cells against hypoxia‐induced cell death by interplaying with hypoxia‐inducible factor 1α and nuclear factor‐kB signaling. This is associated with increased metabolic activities and pro‐survival pathways indicating that Rai plays an important role in the adaptive response of T cells under hypoxia.